Effect of Corporate Governance on Tobin’s Q in Nepalese Commercial Banks - Gurung, Ritika; Upreti, Rekha; Shrestha, Riya; Pradhan, Sumit (Nepalese Journal of Management, 2025)
This study examines the effect of corporate governance on Tobin’s Q in Nepalese commercial banks. Return on assets and Tobin’s Q are selected as the dependent variables. Similarly, board size, audit committee, gender diversity, board independence, institutional ownership and number of meetings are selected as the independent variables. This study is based on secondary data of 15 banks with 105 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial statistics published by Nepal Rastra bank and the annual reports of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on Tobin’s Q in Nepalese commercial banks. The study revealed that board size has a positive impact on return on assets. It means that increase in board size leads to increase in return on assets. Similarly, board size has a negative impact on Tobin’s Q. It means that increase in board size leads to decrease in Tobin’s Q. Likewise, audit committee has a positive impact on return on assets. It shows that large the audit committee size, higher would be the return on assets. In addition, audit committee has a negative impact on Tobin’s Q. It shows that large the audit committee size, lower would be the Tobin’s Q. Moreover, this study showed gender diversity has a positive impact on return on assets and Tobin’s Q. It means that increase in number of female directors in the board leads to increase in return on assets and Tobin’s Q. Further, board independence has a positive impact on return on assets and Tobin’s Q. It shows that higher the number of independent directors in the board, higher would be the return on assets and Tobin’s Q. Likewise, institutional ownership has a positive impact on return on assets and Tobin’s Q. It indicates that increase in institutional ownership leads to increase in return on assets and Tobin’s Q. Similarly, number of meetings has a positive impact on return on assets and Tobin’s Q. It indicates that increase in number of board meetings leads to increase in return on assets and Tobin’s Q.